Public Employment Redux - Pietro Garibaldi; Pedro Maia Gomes; Thepthida Sopraseuth (Institute of Labor Economics (IZA), 2019)
The public sector hires disproportionately more educated workers. Using US microdata, we show that the education bias also holds within industries and in two thirds of 3-digit occupations. To rationalize this finding, we propose a model of private and public employment based on two features. First, alongside a perfectly competitive private sector, a cost-minimizing government acts with a wage schedule that does not equate supply and demand. Second, our economy features heterogeneity across individuals and jobs, and a simple sorting mechanism that generates underemployment – educated workers performing unskilled jobs. The equilibrium model is parsimonious and is calibrated to match key moments of the US public and private sectors. We find that the public-sector wage differential and excess underemployment account for 15 percent of the education bias, with the remaining accounted for by technology. In a counterintuitive fashion, we find that more wage compression in the public sector raises inequality in the private sector. A 1 percent increase in unskilled public wages raises skilled private wages by 0.07 percent and lowers unskilled private wages by 0.06 percent.
Keywords: E24; E62l; J20; J24; J31; J45; 330; public-sector employment; public-sector wages; underemployment; education